An assessment on performance, combustion and emission behavior of a diesel engine powered by ceria nanoparticle blended emulsified biofuel. (1st September 2016) - Annamalai, M.; Dhinesh, B.; Nanthagopal, K.; SivaramaKrishnan, P.; Isaac JoshuaRamesh Lalvani, J.; Parthasarathy, M.; Annamalai, K.
Highlights: A novel biofuel, lemongrass is used as a renewable energy source. Emulsion prepared using 5% of water, 93% of lemongrass oil and 2% of surfactant. Emulsified nano biofuel performance profile stayed closer to diesel fuel. Drastic reduction in HC, CO, NOX and marginal decrease of smoke compared with diesel. Abstract: The consequence of using cerium oxide (CeO2 ) nanoparticle as additive in Lemongrass Oil (LGO) emulsion fuel was experimentally investigated in a single cylinder, constant speed diesel engine. A novel biofuel plant was introduced in this project, namely lemongrass whose binomial name is Cymbopogon flexuosus . The main objective of the project is to reduce the level of harmful pollutants in the exhaust such as unburned hydrocarbon (HC), carbon monoxide (CO), oxides of nitrogen (NOX ), and smoke. The engine performance could also be increased due to the addition of CeO2 nanoparticle. The LGO emulsion fuel was prepared in the proportion of 5% of water, 93% of LGO and 2% of span80 by volume basis. Span80 acted as surfactant and it would reduce surface tension between the liquids with a hydrophilic-lipophilic balance (HLB) value of 4.2. The ceria nanoparticle was dispersed with the LGO emulsion fuel in the dosage of 30 ppm (ppm). The diesel engine performance, combustion behavior and emission magnitude were compared with diesel and LGO as the base fuels. The whole investigation was conducted with a single cylinder diesel engine using the following fuels, namely neat diesel, neat LGO, LGO emulsion and LGO nano emulsion fuels respectively. The LGO emulsion fuel could reduce smoke and NOX emissions and could improve Brake Thermal Efficiency (BTE), Brake Specific Energy Consumption (BSEC) compared with neat LGO despite the marginal increase in HC and CO emissions. For ceria nanoparticle blended test fuel, the drastic reduction of carbon monoxide (CO), unburned hydrocarbon (HC), oxides of nitrogen (NOX ) and marginal decrease of smoke opacity emission could be achieved compared with the LGO emulsion and diesel fuel at various power outputs. Improvement in BTE was also observed for LGO nano emulsion test fuel compared to neat LGO and LGO emulsion fuels due to improved atomization and rapid evaporation rate of fuel owing to large surface area to volume ratio of CeO2 nanoparticle.